Data mining applications for sustainable medical systems : a study on diabetes - Özyazar, Özge (My University, 2019)
Günümüzün gelişen bilişim sistemleri teknolojileri, sağlık kuruluşlarında hasta takip sistemlerinin gelişmesi ile sağlık sektöründe veri madenciliği uygulamalarının yaygınlaşmasını sağlamıştır. Literatürde birçok hastalık ile ilgili veri madenciliği çalışmaları yapılmakta, özellikle hastalarla ilgili detaylı verilerinin oluşu, hastalığın çeşitli tiplerde bulunması (tip 1, tip 2, hamilelik diyabeti) ve komplikasyonlarının ( mikro- , makro-) çok önemli ve etkilerinin mortalite ve imputasyonlara neden oluşu sebebiyle diyabet hastalığı sağlıkta veri madenciliği uygulamalarının odak konusu olmaktadır. Bu çalışmada bir hastahanenin, diyabet ve metabolizma kliniğinin verileri kullanılarak tip 2 diyabet hastalığı üzerine çalışılmıştır. Yapılan retrospektif çalışmada 1160 tip 2 diyabetli hastanın demografik verileri, biokimyasal ve antropometrik verileri, insülin kullanımı, özgeçmiş, soygeçmiş, hipertansiyon hastalığı teşhisi, makro ve mikro hastalıkların teşhisi, hastalık süresi ve Charlson komorbidite indeks (CCI) ölçütü değişken olarak kullanılmıştır. Tıp literatüründen yararlanılarak veri madenciliği çalışmalarında daha önce kullanılmamış yada az kullanılmış tanı ölçütleri kullanılarak literatüre katkı sağlamak hedeflenmiştir. C4.5 karar ağacı algoritması ile sınıflandırma yapılarak makrovasküler ve mikrovasküler komplikasyonlar için risk modelleri oluşturmak, yeni tanısı konulmuş ve takip hastaları üzerine çalışılarak yan hastalıkların teşhisinde tahmin modelleri oluşturmak, hastalık tanı kriterlerinden HbA1c 7.5 değeri eşik değer olarak belirlenerek komplikasyonlar için risk modelleri oluşturmak hedeflenmiştir. Uygulanan veri ön işleme, özellik seçimi ve dengesiz veri ile mücadele etme methodları ile anlamlı sonuçlar elde edilmiştir. Durum modelleri sırası ile 86.21% (Hasta Durumu), 85.63% (HbA1c =7.5), 97.27% (Makrovasküler komplikasyonlar) ve 96.45% (Mikrovasküler Komplikasyonlar) doğruluk değerine ulaşmıştır.

With the development of patient follow-up electronic systems in healthcare, today's developing information technologies have enabled data mining applications to become widespread in the healthcare sector. In the literature, there are many data mining research studies which has focused on various number of diseases, especially diabetes mellitus. Diabetes Mellitus is the focus of data mining practices in health since the disease has subtypes (type 1, type 2, pregnancy diabetes), severe complications (micro-, macro-) those are very important and their effects cause mortality and imputations and diversity of data type. Type 2, is one of the types of diabetes mellitus and is a chronic condition that is usually seen in adults. Type 2 Diabetes is inherently insidious. Most patients can be diagnosed after one or more than one indications of complications are observed. This not only makes it difficult to control the disease, but also increases patient treatment costs. Therefore, it is very important to establish early diagnosis techniques and to identify risk factors and risk groups. In this study, it has been studied on Type 2 Diabetes Mellitus which data were allocated from Diabetes and Metabolism clinic of a hospital. Demographic, biochemical and anthropometric data, insulin usage, backgorund information, family health history, diagnosis of hypertension disease, diagnosis of macrovascular and microvascular complications, disease duration and Charlson comorbidity index (CCI) were used as variables. It is aimed to contribute data mining application literature with using rarely or have not been applied diagnostic features of Diabetes. It is emphasized that, new features played a decisive role for determining the risk models. Creating risk models for macrovascular and microvascular complications by classifying with C4.5 decision tree algorithm, to create prediction models for the diagnosis of side diseases by studying newly diagnosed and follow-up patients and defining HbA1c 7.5, which is one of the diagnostic criteria of the disease, is determined as a threshold value and risk models for complications are targeted with this study. Significant results were obtained with support of applied data preprocessing and imbalance data handling methods. Three selected models showed 86.21% (Patient’s status), 85.63% (
Keywords: CLASSIFICATION; DIABETES; DİYABET DATA MINING; SINIFLANDIRMA; VERİ MADENCİLİĞİ